Impact of single round of low dose CT lung cancer screening on cause of mortality in different socio-economic groups: a post-hoc analysis of long-term follow-up of the UKLS trialResearch in context - Michael P.A. Davies; Daniel Vulkan; Rhian Gabe; Stephen W. Duffy; John K. Field (Elsevier, 2024)
Summary: Background: Lower socioeconomic status, as measured by the Index of Multiple Deprivation (IMD), is associated with higher rates of smoking-related disease mortality, and with poor uptake of cancer screening. Here we explore whether socioeconomic status impacts the effectiveness of a single round of low-dose-CT screening, or impacts other causes of death, in the UKLS LDCT screening trial. Methods: IMD quintiles were defined according to UK-wide data, with the deprived group defined as the lower two quintiles (Q1-2) and the less deprived as Q3-5. Follow-up data was obtained for lung cancer diagnosis (median follow-up 9.1 years) and cause of death (median follow-up 9.9 years). Outcomes were compared based on IMD group and trial arm (CT or control). Findings: More deprived quintiles were less likely to respond to the questionnaire, but this population was more likely to be selected for screening by the LLP risk model. Lower IMD quintiles benefitted from low-dose-CT screening in terms of lung cancer survival (HR 1.89, 95% CI 1.16-3.08) to the same extent as upper quintiles (HR 1.87, 95% CI 1.07-3.26). However, there was a bigger impact on deaths due to COPD and emphysema in more deprived quintiles. Interpretation: Whilst LDCT screening benefit for lung cancer was similar, significant impact on the rates of death from other smoking-related diseases, notably COPD and emphysema, was seen primarily in lower socioeconomic groups. Future research is required to confirm how lung cancer screening benefits other disease outcomes. Funding: NIHR Health Technology Assessment Programme; NIHR Policy Research programme; Roy Castle Lung Cancer Foundation.